Evaluating main gas emission and energy consumption economy during tobacco leaf curing life cycle based on clean energy - Yinlong Zhu; Yonglei Jiang; Yi Chen; Jiaen Su; Ming Li; Qiongfen Yu; Zhenhua Gu; Jianhuan Deng; Sheng Tang; Zhihao Song; Xudong Wang; Bo Ma (Scientific Reports)
Abstract Coal roasters suffer from unstable combustion, resulting in high energy consumption and environmental pollution, this paper explores main gas emissions and energy consumption economy of biomass, alcohol-based and natural gas ovens in order to obtain the best alternative energy source. The paper conducted a comprehensive analysis of the following aspects in clean energy tobacco curing: major gas emission concentrations and volumes at each stage, emission quantities per cubic meter of major gases, gas emissions during the leaf yellowing/color-fixing stage and stem-drying stage of tobacco curing, total lifecycle emissions of major gases and energy consumption efficiency/economic feasibility of the curing facility. Data analysis showed that CO2 emission concentration of each energy roaster reached the highest in all stages under standard working conditions, and CO2 emission of biomass roaster reached 550.68 kg in the 10th stage, while there was no SO2 emission from alcohol-based and natural gas roasters. In addition, the highest total emissions per cubic meter of each of the major gaseous emitters CO2, SO2, NO and NO2 were all biomass, 21.1 kg, 0.057 kg, 0.036 kg and 0.0005 kg, respectively. During the baking process, CO2 emission of natural gas per ton of wet tobacco leaves was only 105.97 kg, with no NO and NO2 emissions, and no SO2 emissions from alcohol-based and natural gas. The emissions of CO2, SO2, NO and NO2 increased gradually in the yellowing period, color fixation period and dry tendon period, and most emissions were in the dry tendon period of biomass roasting room, which were 1203.85 kg, 35.23 kg, 1.53 kg and 0.248 kg, respectively. There was no emission of SO2 in the alcohol-based and natural gas roasting rooms. In addition, biomass had the largest total emissions in the entire life cycle of clean energy tobacco leaf baking. As baking time increases, pollutant emissions also increase. The highest CO2 emissions from biomass were 1518.82 kg. CO2 emission rates of alcohol-based and natural gas baking rooms are relatively slow, and the minimum CO2 emissions from the natural gas baking room were 582.82 kg. The ratio of fresh and dry cigarettes after roasting was roughly around 7:1, with the least consumption of natural gas for fresh tobacco, lower power consumption and a higher average dehumidification ratio per unit of energy consumption. The unit cost of dried tobacco leaves in the biomass curing room was 1.35 yuan, which was 22.3% and 16.2% lower than alcohol-based and natural gas. Although biomass curing barns had the lowest unit cost for dried tobacco leaves, their combustion produces more gas emissions. These results showed that biomass had the largest number of major gas emissions and the largest emission volumes, while natural gas and alcohol genes had lower emissions and better economic performance, which can play a significant role in energy conservation, emission reduction, cost reduction and efficiency improvement.